KINERJA SISTEM PENYAPU TIPE GUTTER BROOMS PADA PROTOTIPE KENDARAAN PENYAPU JALAN - Aditya Bayu Pratama; Sugiyanto Sugiyanto; Radhian Krisnaputra; Benidiktus Tulung Prayoga; Yosephus Ardean Kurnianto Prayitno; Isworo Djati (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2023)
The performance of the gutter brooms sweeping system was studied by conducting an experimental sweeping test. The test is carried out by operating a sweeper system to sweep plastic, paper, and leaf waste. The test results show that at a broom rotation speed of 150,6 rpm, the sweeping of plastic obtained a 100% sweeping success rate with the three settings for the height of the broom, while the sweeping of leaf waste obtained a 100% sweeping success rate at the broom position Â± 0 mm touching the road surface and the sweeping of paper waste obtained a 100% sweeping success rate at the broom position Â± 15 mm pressing the road surface. The comprehensive system of the gutter brooms type of road sweeper vehicle prototype can show sweeping performance with a 100% success rate, although the success rate of the sweeping is uncertain for different sweeping situations.